Equivalence of silver and gold nanoparticles for dose enhancement in nanoparticle-aided brachytherapy. (30th August 2019) - Kakade, Nitin R; Kumar, Rajesh; Sharma, S D; Datta, D
Abstract: The goal of radiotherapy is to deliver a clinical dose to the tumor while sparing the surrounding healthy tissues. The problem associated with radiotherapy is the lack of selectivity between the tumor and the healthy tissue. The methodology for depositing a higher dose selectively in the tumor region by making tumor radio-sensitive with the infusion of nanoparticles (NPs) is being evolved. Several materials have been explored for NP-aided radiotherapy. Gold and silver NPs have been studied in more detail. However, silver is relatively less expensive and the use of silver NP-aided radiotherapy may be an economical choice. The dose enhancement factor (DEF) for gold and silver with mono-energetic photons having energy from 20 keV to 500 keV were computed using a theoretical method to confirm the suitability of the silver as a substitute for gold NPs. The optimal energy to achieve the similar dose enhancement with silver and gold is found to be 50–70 keV. The 170 Tm brachytherapy source was identified as the source with optimum energy to achieve the same level of dose enhancement using both NPs. The DEF in the prostate region was calculated using the Monte Carlo method for 170 Tm source. The DEFs of 1.94 ± 0.01 and 1.92 ± 0.01 were recorded at a fixed concentration of 7 mg of gold and silver NPs inside per gram of tumor respectively. The use of silver NPs instead of gold NPs is a cost effective option for the treatment of prostate cancer with 170 Tm brachytherapy source.